Measuring the extent of a high performance work system: A mixed methodology approach - B. Nicole Rasool; Muhammad Nouman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
High performance work systems (HPWS) and their effect on firm performance is examined using a single holistic case study design in which the Total Strategic Resource Approach (TSRA) is used to measure the extent of HPWS implementation in a private Pakistani hospital. Using a mixed methodology case approach, it is discovered that Pakistan Hospital & Medical College (PHMC) has begun to implement aspects of an HPWS. Profound weaker human resource areas include information sharing and compensation although improvement is needed in all 12 HR practice areas. Firm performance was measured using perceptual measures of the organization's employees, and it was determined that the HPWS does have a significantly positive effect on firm performance. The study was also designed to test the reliability of the TSRA for the Pakistani context given its unique cultural setting, and it was confirmed that the TSRA is a reliable model that future researchers can use in order to measure the extent of HPWS implementation in other Pakistani organizations.
Keywords: 330; high performance work system (HPWS); firm performance; total strategic resource approach (TSRA); resource-based view; organizational performance